2020
DOI: 10.3390/vaccines8010088
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Partial Envelope Domain II into Envelope Domain III of Dengue Virus Antigen Potentiates the Induction of Virus-Neutralizing Antibodies and Induces Protective Immunity

Abstract: Dengue virus (DENV) comprises four serotypes in the family Flaviviridae and is a causative agent of dengue-related diseases, including dengue fever. Dengue fever is generally a self-limited febrile illness. However, secondary infection of patients with a suboptimal antibody (Ab) response provokes life-threatening severe dengue hemorrhagic fever or dengue shock syndrome. To develop a potent candidate subunit vaccine against DENV infection, we developed the EDII-cEDIII antigen, which contains partial envelope do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For further studies, it would be interesting to directly compare the neutralizing antibody response of DENV1 VLPs with E‐DIII displaying hepatitis B particles, because the production of neutralizing antibodies in humans is not limited to the EIII region but rather involves the quaternary structures formed by E protein multimers (de Alwis et al ., 2012; Wahala et al ., 2009). Furthermore, the extension of the EIII domain subunit with a part of the E domain II led to improved neutralizing antibody titre (Park et al ., 2020), indicating that the use of VLPs displaying the whole E protein is likely to be the most suitable DENV vaccine strategy, provided that prM cleavage and maturation of VLPs can be achieved to avoid the production of non‐neutralizing, but enhancing antibodies. In fact, we attempted to display the entire DENV1 E ectodomain on the surface of tandem hepatitis B core particles to compare this external antigen display strategy with our DENV1 VLPs, but we were unable to produce such full‐length E‐displaying HBcAg CLPs.…”
Section: Discussionmentioning
confidence: 99%
“…For further studies, it would be interesting to directly compare the neutralizing antibody response of DENV1 VLPs with E‐DIII displaying hepatitis B particles, because the production of neutralizing antibodies in humans is not limited to the EIII region but rather involves the quaternary structures formed by E protein multimers (de Alwis et al ., 2012; Wahala et al ., 2009). Furthermore, the extension of the EIII domain subunit with a part of the E domain II led to improved neutralizing antibody titre (Park et al ., 2020), indicating that the use of VLPs displaying the whole E protein is likely to be the most suitable DENV vaccine strategy, provided that prM cleavage and maturation of VLPs can be achieved to avoid the production of non‐neutralizing, but enhancing antibodies. In fact, we attempted to display the entire DENV1 E ectodomain on the surface of tandem hepatitis B core particles to compare this external antigen display strategy with our DENV1 VLPs, but we were unable to produce such full‐length E‐displaying HBcAg CLPs.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted using the Easy-BLUE Total RNA extraction kit (Intron Biotechnology, Sungnam, Korea) and converted into cDNA using a reverse-transcription reaction system (Promega, Fitchburg, WI, USA). Quantitative real-time PCR analyses were performed using SsoAdvanced Universal SYBR Green Supermix (Bio-Rad Laboratories, Hercules, CA, USA) with the CFX Connect Real-Time PCR Detection System (Bio-Rad), as described previously [ 17 ]. Gene expression was normalized against a β-actin internal control gene.…”
Section: Methodsmentioning
confidence: 99%
“…In this Issue, Park et al outlines a candidate subunit vaccine based on eliciting a strong neutralizing antibody response against E DIII. This vaccine was developed to combat all four DENV serotypes by combining two subunits: partial envelope domain II and consensus envelope domain III (cEDIII) [ 10 ]. The authors found that an antibody purified from mice following immunization with this combined candidate vaccine was strongly neutralizing compared to their single subunit vaccine containing only cEDIII, with limited non-neutralizing antigen-specific antibody [ 10 ].…”
mentioning
confidence: 99%
“…This vaccine was developed to combat all four DENV serotypes by combining two subunits: partial envelope domain II and consensus envelope domain III (cEDIII) [ 10 ]. The authors found that an antibody purified from mice following immunization with this combined candidate vaccine was strongly neutralizing compared to their single subunit vaccine containing only cEDIII, with limited non-neutralizing antigen-specific antibody [ 10 ]. In addition, this combined subunit vaccine was able to reduce DENV titers in several tissues when compared to the single subunit vaccine, and conferred protection against DENV1, 2 and 4 in murine challenge models, thus showing promise as a candidate DENV subunit vaccine [ 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation